The Influence of Shade Tree Diversity on Natural Enemy Communities and Microclimate in Coffee Agroforestry Systems - Dewi, Nilasari; Kurnianto, Agung Sih; Haryadi, Nanang Tri; Rosita, Mitayuni Faur; Guretno, Titus Krido; Febrianti, Wanda Hamidah Zakiyah; Khowatini, Husnul; Priambodo, Bagus (The Journal of Experimental Life Science, 2025)
Coffee agroforestry is an integrated farming system that combines coffee cultivation with the planting of shade trees. While it is well-established that vegetation diversity can support populations of natural enemies, few studies have investigated how varying levels of vegetation diversity interact with microclimatic conditions to influence insect community dynamics. Conducted in Desa Pace, Jember, East Java, the research compares simple and complex agroforestry systems in terms of their vegetation structure and the resulting impacts on natural enemy diversity. Field sampling was carried out in May, July, and September using yellow pan traps, accompanied by microclimatic measurements. Results revealed that the simple agroforestry had greater vegetation diversity. However, the Shannon-Wiener Index for vegetation was 0.94 in the complex system and 0.56 in the simple system, while the diversity of natural enemies was identical (1.70) in both systems. Microclimatic factors played a key role, with the simple having higher humidity and the complex exhibiting higher temperatures. These findings underscore that higher vegetation diversity does not always correspond to increased diversity among natural enemies, pointing to the influence of other ecological and environmental factors in shaping these communities. The study highlighted the importance of selecting appropriate shade vegetation to support sustainable and climate-resilient coffee agroforestry systems.